Are sleep duration and sleep quality associated with diet quality, physical activity, and body weight status? A population-based study of Canadian children - Khan, Mohammad K. A.; Chu, Yen Li; Kirk, Sara F. L.; Veugelers, Paul J. (Canadian journal of public health, 2015)
OBJECTIVES:To describe sleep duration and sleep characteristics, and to examine the associations between sleep duration and characteristics and body weight status, diet quality, and physical activity levels among grade 5 children in Nova Scotia. METHODS:A provincially representative sample of 5,560 grade 5 children and their parents in Nova Scotia was surveyed. Parents were asked to report their child's bedtime and wake-up time, and to indicate how often their child snored or felt sleepy during the day. Dietary intake and physical activity were self-reported by children using the Harvard Youth/Adolescent Food Frequency Questionnaire and the Physical Activity Questionnaire for Children respectively. Body weight status was determined using measured heights and weights. Linear and logistic random effects models with children nested within schools were used to test for associations. RESULTS:Approximately half of the surveyed parents reported that their children were not getting adequate sleep at night. Longer sleep duration was statistically significantly associated with decreased risk for overweight and obesity independent of other sleep characteristics (OR = 0.82, 95% CI: 0.73, 0.91). Longer sleep duration was also associated with better diet quality and higher levels of physical activity. CONCLUSIONS:These findings indicate a need for health promotion strategies to encourage adequate sleep and to promote healthy sleep environments among children. Given the links among sleep, body weight status and lifestyle behaviours, these messages should be included in public health interventions aimed at preventing obesity and promoting health among children.